Bioguided Isolation and Structure Identification of Acetylcholinesterase Enzyme Inhibitors from Drynariae Rhizome - Ming-Yang Liu; Fan Zeng; Yue Shen; Yu-Ying Wang; Ning Zhang; Fang Geng (Journal of Analytical Methods in Chemistry)
Drynariae Rhizome, widely distributed in southern China, was clinically used as a traditional treatment for cognitive disfunction, such as Alzheimer’s disease (AD). The aim of our work was to evaluate the AChE inhibition activities of extracts of Drynariae Rhizome and pure compounds using a bioguided fractionation procedure. The classical approach for screening potential AChE inhibitors was developed by Ellman. However, the background color of compounds or herb extracts remained uncertain and frequently interfered with the detection of the secondary reaction, thereby easily yielding false positive or false negative results. Here, a high-throughput assay monitoring the transformation of iodized choline from iodized acetylcholine catalyzed by AChE was established based on UPLC-MS/MS. The bioguided fractionation of the extract using this method resulted in the isolation of eight AChE inhibitory flavonoids, including naringenin, eriodictyol, kaempferol, luteolin, astragalin, luteolin-7-O-β-D-glucoside, naringin, and neoeriocitrin, with the IC50 values of 3.81 ± 0.21 μM, 7.19 ± 0.62 μM, 11.09 ± 1.02 μM, 17.26 ± 0.23 μM, 18.24 ± 2.33 μM, 17.13 ± 1.02 μM, 26.4 ± 1.17 μM, and 22.49 ± 1.25 μM. It is assumed that the identified flavonoids contribute to the AChE inhibition activity of Drynariae Rhizome. These results are in agreement with the traditional uses of Drynariae Rhizome for AD.